NILAI-NILAI LUHUR PUJANGGA JAWA DALAM SERAT SANA SUNU - Widyatwati, Ken (Faculty of Humanities, Diponegoro University, 2012)
ABSTRACT One form of Indonesian cultural heritages is manuscript containing supreme and perennial ideas. Those manuscripts may be found throughout the archipelago, both in Malayan and Javanese. Sana Sunu is one of well-known Javanese manuscripts. This paper analyzes its content with pragmatic theory which gives priority to purpose value from the work of literature. This research uses philology method, including manuscript stock, manuscript description, transliteration, and analysis presentation in a descriptive manner. It is then found that Serat Sana Sunu contains messages about good behavior, noble character, commanding people to always work and study hard to get success in life, and reminding them to remember adhering to Rukun Islam in order to preserve life harmony with society and environment. These are such important messages to Indonesia current situation. Keywords: Serat Sana Sunu, pragmatic theory, philology method Â